Eksplorasi Metode Penginjilan Gereja Bala Keselamatan Sebagai Model Untuk Menjangkau Suku Kaili Da’a Di Palu Sulawesi Tengah - Kristiana Fitriani (Jurnal Teologi dan Pelayanan Kerusso, 2019)
The Kaili are a native of Palu - Central Sulawesi and are one of the target groups for sharing the gospel. According to observations and empirical data in the field, the Kaili tribe consists of three groups with a variety of cultures. The three groups are often referred to as the Da'a, the Ledo and the Tara. In terms of religion and belief, there are very striking differences. The Kaili Da'a are almost entirely Christian. The Kaili Ledo people, only a small proportion are Christians, some are Muslim and ethnic beliefs. The people of Kaili Tara are almost entirely Muslim, in fact almost none are Christians. The existence of the majority Christian Kaili Da'a is the success of the Salvation Army church in carrying out their mission to preach the Gospel. There are a number of principles, methods and approaches that have been carried out by the Salvation Army in this regard. This makes the Salvation Army the largest church in Palu, and has the most extensive service area compared to other churches. The number of small church opened up to the mountain peaks is evidence of the success of this church in carrying out world missions. An exploratory study of the evangelistic methods of a church that has proven successful in carrying out the mission of evangelism is very important. It is said so, because through this study one can learn how a church begins evangelistic activities, what methods it has used, what obstacles it has passed until the church has succeeded in preaching the gospel to a community group. Preaching the gospel for the Kaili tribe is something very important to do. In front of us there is still another group that has various similarities with Kaili Da'a people who do not know the gospel. The Kaili Tara people and some Kaili Ledo people also need to hear the gospel message. The success of the Salvation Army Church in reaching the Kaili Da'a will be a case study, especially for finding effective evangelistic patterns or methods for other Kaili tribes. The first step in this study was carried out by analyzing the Evangelical Church evangelistic model of the Kaili Da'a tribe. The results of the analysis of the model provide answers to the search for relevant methods to preach the gospel among other Kaili tribes who have not yet heard the gospel. Second, implement evangelistic strategies or patterns that are used to serve as models for evangelizing other Kaili tribal groups. It is hoped that someone or an evangelistic organization that will evangelize the Kaili tribe will not get too many difficulties, because there is already a model that can be used as a guide. The use of methods in scientific research is very important. Therefore, the writing of this scientific paper will use two methods. The two methods are: first, library research method. The procedure adopted in this case is by reading books or articles relating to evangelism by the Salvation Church, reading books written by experts regarding the topic of evangelistic service, and reading books directly related to the topic of discussion Second, field research methods. In this method will use participan obvervation procedures and interviews with people involved in Salvation Army church evangelism activities. In addition, by looking for reliable data regarding the results of evangelism conducted by the alvation Army stionnaires containing questions related to the topic of discussion will be distributed to Salvation Army church leaders and activists directly related to the evangelistic ministry and will be returned to the author for further processing. From the field research through the questionnaire it was concluded that the most instrumental aspect in evangelizing the Kaili Da'a tribe was through the visit of officers, then personal evangelism by the officers and also through the testimony of the Salvation Church. It is evident that the service of the officers has a very important role in evangelizing the Kaili tribe. That is why the author advised the Salvation Army to improve the quality of officers. Provisioning and training as well as increasing the resources of the officers should be carried out in a consistent and directed activity. In general, the authors see that the Salvation Army succeeded in introducing and guiding the Kaili Da'a community to accept the Lord Jesus as their personal Lord and Savior. Furthermore, the authors advise that these service activities be continued in a directed and consistent manner. In addition, pastoral care of the congregation that has accepted the Lord Jesus needs to be improved so that the congregation's understanding of Jesus grows and the Church becomes a strong believer in facing all the challenges of life.